UTILIZATION OF AESTHETIC INSTRUMENTS WITHIN THE COMPOSITION - Rustamov Ilkhom Tursunovich (TADQIQOTLAR.UZ, 2024)
Abstract: This article delves into the utilization of aesthetic tools within artistic compositions, elucidating the methods through which creators utilize diverse instruments to amplify the aesthetic caliber and influence of their creations. Through an examination of pertinent scholarly sources and critical discussions, this research scrutinizes the array of techniques and approaches employed by artists across varied artistic mediums to attain aesthetic objectives.